Melanoma metastasis: what role does melanin play? (review) - Saud, Anoosha; Sagineedu, Sreenivasa R.; Ng, Hui-Suan; Stanslas, Johnson; Chee, Jonathan Woei Lim (Spandidos publication, 2022)
Melanoma is an extremely aggressive form of skin cancer that can spread to the lungs, brain, and liver, among other vital organs. Melanoma cells, unlike any other cancer cells, can produce significant amounts of melanin by a process known as melanogenesis, causing them to become heavily pigmented. Melanogenesis, specifically the melanin pigment, is well known for its ability to protect the skin from the harmful effects of UV light, which can lead to the development of skin cancer. Nevertheless, uncontrolled melanogenesis plays a role in the advancement of melanotic melanoma, and melanin pigments can reduce the effectiveness of radiotherapy and immunotherapy. Therefore, studies are being performed that focus on inhibiting melanogenesis to prevent melanoma metastasis. However, it is worth noting that, in addition to its UV‑protective function, melanin also plays a role in preventing melanoma metastasis. Microphthalmia‑associated transcription factor (MITF) and melanin have been demonstrated to attenuate the aggressiveness of melanoma by suppressing numerous essential metastatic processes. Eumelanin and pheomelanin (two types of melanin), which cause oxidative stress, can also prevent melanoma progression in the early stages. Hence, it is vital to explore the role of inducing melanogenesis rather than inhibiting melanogenesis in preventing melanoma metastasis.